Aphicidal Activity of an Ageraphorone Extract From Eupatorium adenophorum Against Pseudoregma bambucicola (Homoptera: Aphididae, Takahashi). Issue 1 (25th June 2015) - Nong, Xiang; Chen, Feng-Zheng; Yang, Yao-Jun; Liang, Zi; Huang, Bao-Lian; Li, Yi; Liu, Tian-Fei; Yu, Hua
Abstract : The bamboo aphid, Pseudoregma bambucicola, is an important insect pest of bamboo that affects normal bamboo growth and induces sooty molds. The control of P. bambucicola involves the application of chemicals, such as imidacloprid, to which many species are resistant. In this study, we isolate a novel botanical pesticide (9-oxo-10, 11-dehydro-ageraphorone) from an Eupatorium adenophorum (Asteraceae: Compositae) petroleum ether extract and test the aphicidal activity of this compound against P. bambucicola in laboratory bioassay and field-based experiments. This ageraphorone compound at a concentration of 2 mg/ml caused 73.33% mortality (corrected mortality [Subtracted the mortality of the negative control]: 70%) of P. bambucicola by laboratory bioassay within 6 h. Even at lower concentrations, this compound caused greater 33% mortality (corrected mortality: 30%) of aphids. Field experiments with naturally infested bamboo plants showed that two applications of 2 mg/ml ageraphorone to infested plants completely cleared infestations within 30 d. These effects were similar to those of the positive control (imidacloprid). These results reveal that 9-oxo-10, 11-dehydro-ageraphorone exhibits significant aphicidal activity against bamboo aphids. We suggest that future research be directed at developing this ageraphorone compound from E. adenophorum as an aphicidal agent for biocontrol.